Generalized Neutrosophic TOPSIS to Solve Multi-Criteria Decision-Making Problems - Rana Muhammad Zulqarnain; Xiao Long Xin; Muhammad Saeed; Florentin Smarandache; Nadeem Ahmad (Neutrosophic Sets and Systems, 2020)
Multi-criteria decision making (MCDM) is the technique of selecting the best alternative from multiple alternatives and multiple conditions. The technique for order preference by similarity to an ideal solution (TOPSIS) is a crucial practical technique for ranking and selecting different options by using a distance measure. In this article, we protract the fuzzy TOPSIS technique to neutrosophic fuzzy TOPSIS, and prove the accuracy of the method by explaining the MCDM problem with single-value neutrosophic information, and use the method for supplier selection in the production industry. We hope that this article will promote future scientific research on numerous existence issues based on multi-criteria decision making.